Influence of energy willow crops on soil features in the case of a contaminated land - MUȘAT Elena Camelia (JOURNAL OF ENVIRONMENTAL PROTECTION AND ECOLOGY, 2018)
The present paper aims to highlight the influence of energy willow growing on a land contaminated with heavy metals on the features of the soil and its minerals. For this purpose, soil profiles from the crop planting year and after two years were realised. The samples were taken from different depths and they were subjected to some investigations by using specific pedologic equipment. A series of parameters such as the soil reaction, the humus content, the ratio carbon/nitrogen (C/N), the content of sodium, nitrogen, phosphorus and potassium were determined. As a result of data interpretation, a considerable decrease of the sodium content for the first 10 cm (which is close to the higher admissible limit) and an increase of the content of nitrogen, phosphorus and potassium were noticed.
Keywords: willow; soil features; contaminated land